An unexpected epigraph: exploring the personal and philosophical relevance of Ralph Waldo Emerson to Carl Ransom Rogers. (3rd July 2022) - Dalton, Emily
ABSTRACT: This article takes as its starting point the Emerson epigraph chosen by Rogers for his seminal book Client-Centered Therapy, and discovers that Rogers also acknowledged the 'deep influence' that Emerson and the transcendental school had on his personal life and philosophy. It proposes evidence of this influence, noticing similarities in the writings and biographical details of the two men. It also extrapolates a question and proposes it for further research – the possibility that Rogers integrated Emersonian thinking into the development of the person-approach. The limited and interpretive reasoning for such an extrapolation is acknowledged. The article concludes that Emerson was one of many writers in literature, theology, philosophy, psychology, art and science with whom Rogers engaged over his lifetime, an eclectic contributed to Rogers' fluid, ongoing, and ever-evolving creative synthesis. It also concludes that the question of whether Rogers' use of the epigraph at the beginning of Client-Centered Therapy indicates a connection between Emerson and Rogers' person-centered theory, is worthy of being asked.